Ensuring regional security in the Middle East region in the context of globalization - Assistant Murtalibova Malika Mirmaksudovna (Genius Journals, 2024)
This article examines the relevance of the security problem in the Middle East region and how the processes taking place in the Middle East region are inextricably linked with neighboring countries. In addition, the benefits of the world's leading countries from this region will be analyzed.
Keywords: Türkiye; European Union; Middle East; Russia